Muhamed Fadil-pasha Šerifović as calligraph – hattat - Teparić, Meliha (Anali Gazi Husrev-Begove biblioteke, 2016)
This paper presents the calligraphic work of Muhamed Fadil-pasha Šer- ifović. Although being recognized as politician, kadi, poet, and sheikh, his activities in calligraphy and the fact that he was an excellent calligrapher – hattat, are less known. It includes his diploma in calligraphy –ijazatnam- ah, and five tarikhs that he had composed. Three of them are kept in Gazi Husrev-bey’s Library as part of its Museum exhibition. The inscriptions had probably been engraved according to Šerifović’s calligraphic drawings. Their authorship shall be determined based on the analysis of his so far discovered lawhas that the public is not yet familiar with.